1997
DOI: 10.1111/1468-2389.00056
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Selection Ratio on Perceptions of the Fairness of a Selection Test Battery

Abstract: This research examined the effects of the selection ratio on applicants' perceptions of the fairness of a battery of tests. These fairness perceptions were also examined to assess whether they moderated the validity of the tests. A laboratory study was undertaken to examine the effects of the selection ratio on applicants going through a selection process and to examine the effects of being hired or rejected. Results revealed that the selection ratio did not have an effect on perceptions, but that hired indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…found that selection fairness related to later reapplication among rejected applicants. Thorsteinson and Ryan (1997) found that selection fairness related to the validity of a cognitive ability test but not of a personality test; similarly, other research (Chan, 1997;Chan, Schmitt, Sacco, & DeShon, 1998b) found that fairness was related to cognitive ability test performance but not to personality test performance. However, consistent relationships have not been found between selection fairness and applicant withdrawal (e.g., Schmit & Ryan, 1997;Truxillo et al, 2002) and later commitment and/or satisfaction (e.g., Ambrose & Cropanzano, 2003;Cunningham-Snell et al, 1999), and no relationship has been found with job performance (Gilliland, 1994) or later turnover among those hired (Truxillo et al, 2002).…”
Section: Selection Fairness: Effects On ''Hard'' and ''Soft'' Outcomesmentioning
confidence: 75%
“…found that selection fairness related to later reapplication among rejected applicants. Thorsteinson and Ryan (1997) found that selection fairness related to the validity of a cognitive ability test but not of a personality test; similarly, other research (Chan, 1997;Chan, Schmitt, Sacco, & DeShon, 1998b) found that fairness was related to cognitive ability test performance but not to personality test performance. However, consistent relationships have not been found between selection fairness and applicant withdrawal (e.g., Schmit & Ryan, 1997;Truxillo et al, 2002) and later commitment and/or satisfaction (e.g., Ambrose & Cropanzano, 2003;Cunningham-Snell et al, 1999), and no relationship has been found with job performance (Gilliland, 1994) or later turnover among those hired (Truxillo et al, 2002).…”
Section: Selection Fairness: Effects On ''Hard'' and ''Soft'' Outcomesmentioning
confidence: 75%
“…This is notable because, as Burns, Siers, and Christiansen (2008) indicate, "Over the past two decades convincing evidence has emerged that links applicant reactions to important organizational outcomes" (p. 73). For example, negative applicant reactions to a selection procedure may lower test performance (Chan, Schmitt, Sacco, & DeShon, 1998) and test taker motivation (Smither et al, 1993), which in turn attenuates both the validity and utility of the selection instrument (Thorsteinson & Ryan, 1997). Negative applicant reactions may cause applicants to withdraw from the selection process (Schmit & Ryan, 1997) and may impact not only the pursuit and acceptance of job offers (Macan, Avedon, Paese, & Smith, 1994;Murphy, 1986) but also the willingness to reapply in the future (Gilliland et al, 2001).…”
Section: Applicant Reactions To Selection Proceduresmentioning
confidence: 99%
“…We measured CPPF in the survey with a standardized (mean = 0, standard deviation = 1) three‐item scale: ‘Generally, the process used by the organization in making the hiring decision was fair’, ‘It was not fair how the individual obtained the position [reversed]’, and ‘The organization was concerned about being fair when it hired the individual.’ While we tailored the items to our hiring situation, they are based on Gilliland's () hiring decision fairness scale—a scale adapted and used by other researchers (Thorsteinson and Ryan ). We captured item responses on a 7‐point Likert scale.…”
Section: Methodsmentioning
confidence: 99%
“…While we tailored the items to our hiring situation, they are based on Gilliland's (1994) hiring decision fairness scalea scale adapted and used by other researchers (Thorsteinson and Ryan 1997). We captured item responses on a 7point Likert scale.…”
Section: Measurementmentioning
confidence: 99%